2014
DOI: 10.1128/cvi.00324-14
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Mycobacterium bovis Bacillus Calmette-Guérin Vectors Prime for Strong Cellular Responses to Simian Immunodeficiency Virus Gag in Rhesus Macaques

Abstract: cLive attenuated nonpathogenic Mycobacterium bovis bacillus Calmette-Guérin (BCG) mediates long-lasting immune responses, has been safely administered as a tuberculosis vaccine to billions of humans, and is affordable to produce as a vaccine vector. These characteristics make it very attractive as a human immunodeficiency virus (HIV) vaccine vector candidate. Here, we assessed the immunogenicity of recombinant BCG (rBCG) constructs with different simian immunodeficiency virus (SIV)gag expression cassettes as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…5D). Previously, we described an earlier generation of rBCG vectors that generated strong SIV Gag immune responses in primates (76). Those studies were conducted using bacteria that were freshly grown prior to each immunization and relied on antibiotic selection.…”
Section: Discussionmentioning
confidence: 99%
“…5D). Previously, we described an earlier generation of rBCG vectors that generated strong SIV Gag immune responses in primates (76). Those studies were conducted using bacteria that were freshly grown prior to each immunization and relied on antibiotic selection.…”
Section: Discussionmentioning
confidence: 99%
“…The monkeys were part of an immunogenicity study that aimed to assess the ability of novel rBCG vectors with various SIVmac251 gag -expression cassettes as priming vectors to enhance SIV-specific CD8 + cellular responses upon boost immunization, as we recently described [12]; the previous study did not include an evaluation of vector-specific immunity. Prior to study start, the macaques showed a negative TB skin test against purified protein derivative (PPD).…”
Section: Methodsmentioning
confidence: 99%
“…Each expressed a codon-optimized transgene SIVmac239 gag on a multicopy episomal pMV261 plasmid [12], with a 60-kDa heat shock protein promoter, a human influenza hemagglutinin tag for detection, and a hygromycin resistance marker. Whereas the pSL10-SIVgag expression cassette used an antigen 85 secretion signal, the pSL7-SIVgag employed a 19kDa signal sequence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations